Characteristics of vegetation as determinant of Timor Friarbird (Philemon inornatus) distribution in Bipolo Lanscape of West Timor Island, Indonesia - Blasius Paga; SATYAWAN PUDYATMOKO; LIES RAHAYU WIJAYANTI FAIDA; IGN. PRAMANA YUDA; NURPANA SULAKSONO (Society for Indonesian Biodiversity, 2021)
Abstract. Paga B, Pudyatmoko S, Faida LRW, Yuda IP, Sulaksono N. 2021. Characteristics of vegetation as determinant of Timor Friarbird (Philemon inornatus) distribution in Bipolo Landscape of West Timor Island, Indonesia. Biodiversitas 22: 2617-2635. This study aims to identify vegetation factors as determinants of the distribution of Timor Friarbird (Philemon inornatus) in Timor Island. Timor Friarbird is one of the seven endemics bird species widely distributed in Timor Island, from the eastern region of Timor Leste to western region of Indonesia. This research was conducted at Bipolo Landscape, located in Timor Island, and has diversity of tropical flora diversity surrounding its Natural Tourism Park, which provides Timor Friarbird habitat. The characteristics of vegetation ecology were obtained by sampling design through Biogeography Branch's Sampling Design Tool for ArcGIS, while land use cover type was obtained by maximum likelihood method. The structure and composition of vegetation were observed through nested plot sampling, while Timor Friarbird species were assessed using the combination of point count and line transect method. The result obtained was formulated by discriminant linear regression. The vegetation parameters influencing the presence of Timor Friarbird were tree land use cover, number of trees and their species, pole land use cover, number of poles and their species, sapling land use cover, number of saplings and their species. Timor Friarbird is more likely to be present in the land cover area of poles with a minimum number of individual trees, poles, and saplings (press value Q = 6,63 ? 7). The results of discriminant analysis obtained a new group (nine variables), used collectively as a determinant factor for the presence of Timor Friarbird in their natural habitat on Timor Island